The feasibility of using public-private partnership mechanisms to improve the quality of secondary ambulatory care - V. V. Kravchenko (Kazimierz Wielki University, 2017)
Introduction. Today, inadequate health care system has been formed in the country with insufficient funding and lack of radical changes. The need for solving these problems made it necessary to develop a set of measures that go beyond the competences and financial capabilities of the state and the share of sectors, which allowed the formation of a public-private partnership institute. Objective: To explore the feasibility of mechanisms and private-public partnerships to improve the quality of secondary ambulatory care. Materials and methods: The study was performed using the method of system approach and analysis. The information base for its realization was the scientific works of foreign and domestic specialists, normative documents on the problem, as well as the results of their own research. The results of the study. Today it is clear that the modernization of the public sector of the health care system in terms of its financing and management can be carried out only with the participation of business. The transition to the use of PPP mechanisms in the secondary ambulatory care system, in particular, in the organization of the work of consulting and diagnostic centers, will significantly improve the situation by using additional investments, optimizing costs and creating conditions for technological breakthrough and stable development of the KCC, will create conditions for ensuring effective targeted use of resources, increasing availability and quality of medical care to the population.